Surveying UW-Eau Claire Campus for the Presence of Methicillin Resistant Staphylococcus aureus - Schiedler, Sara; Peterson, Rachelle (My University, 2011)
This study surveyed the UW-Eau Claire campus for the presence of MRSA.
Color poster with text, tables, and images.
Keywords: Methicillin resistance; Staphylococcus aureus; Diagnosis, Laboratory; Posters